2020
DOI: 10.1101/2020.05.28.122184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATP-binding cassette protein ABCF1 couples gene transcription with maintenance of genome integrity in embryonic stem cells

Abstract: OCT4 and SOX2 confer pluripotency by recruiting coactivators to activate stem cell-specific gene expression programs. However, the composition of coactivator complexes and their roles in maintaining stem cell fidelity remain unclear. Here we report the identification of ATP-binding cassette subfamily F member 1 (ABCF1) as a critical coactivator for OCT4/SOX2. ABCF1 is required for pluripotency gene expression and stem cell self-renewal. ABCF1 binds co-dependent coactivators XPC and DKC1 via its intrinsically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 117 publications
(213 reference statements)
0
4
0
Order By: Relevance
“…Most if not all of the regulatory factors described thus far are utilized by many transcription factors to activate their target genes in both ESCs and somatic cells. Our work and others indicated that robust transcriptional activation by OCT4 and SOX2 in ESCs requires additional coactivators that are distinct from Mediator[ 30 , 86 - 88 ]. Using a fully reconstituted in vitro transcription assay, we detected multiple novel coactivators that work in concert with OCT4 and SOX2 to activate pluripotency gene transcription.…”
Section: Lcds In Transcriptional Activation and Repression In Escsmentioning
confidence: 61%
See 3 more Smart Citations
“…Most if not all of the regulatory factors described thus far are utilized by many transcription factors to activate their target genes in both ESCs and somatic cells. Our work and others indicated that robust transcriptional activation by OCT4 and SOX2 in ESCs requires additional coactivators that are distinct from Mediator[ 30 , 86 - 88 ]. Using a fully reconstituted in vitro transcription assay, we detected multiple novel coactivators that work in concert with OCT4 and SOX2 to activate pluripotency gene transcription.…”
Section: Lcds In Transcriptional Activation and Repression In Escsmentioning
confidence: 61%
“…In addition, the flexible nature of LCDs is thought to facilitate their interaction with multiple protein partners, by rapidly adopting an ensemble of conformations[ 27 , 28 ] Indeed, LCD’s ability to bind multiple proteins, also known as multivalency, is a major driving force of LLPS by lowering threshold concentration[ 29 ]. It is worth emphasizing that while LCDs are unstructured sequences, they do not always bind promiscuously to any proteins; instead, they can be selective for binding partners[ 30 - 32 ]. More importantly, because these selective multivalent interactions are usually weak and transient, as opposed to the high affinity (but low valency) “lock-and-key” interactions found in ligand-receptor complexes, they allow dynamic regulation of LLPS properties, condensate composition, and biochemical reactions that take place inside these bodies.…”
Section: Phase Separation Of Proteins Containing Intrinsically Disordered Regionsmentioning
confidence: 99%
See 2 more Smart Citations